Using IMS VDEX in Agrega - Sarasa, Antonio; Canabal, Jose Manuel; Sacristan, Juan Carlos; Jimenez, Raquel (International Journal of Emerging Technologies in Learning (iJET), 2009)
An essential element in a learning object repository is the meta-information associated with the resources housed by the repository, as this is what enables the objects to be retrieved. In many cases, the meta-information which is described consists of the classification of a resource in relation to a taxonomy or thesaurus. Agrega is a network of learning object repositories in which an LOM profile, called LOM-ES, has been used to label the objects. Part of the meta-information described corresponds to the classification of the object with respect to a group of taxonomies and a thesaurus, which have had to be described using the ims vdex standard to enable them to be managed from the federation nodes. This article describes the way in which ims vdex has been used in order to create this description and how these metadata instances are managed.